Impact of adjuvant radiation therapy after definitive surgery in senior adults >80 years old with advanced head and neck squamous cell carcinoma on overall survival - Butkus, Joann M.; Crippen, Meghan; Bar-Ad, Voichita; Luginbuhl, Adam (Frontiers in Oncology, 2022)
Background Adjuvant radiotherapy (RT) following surgical resection confers a survival benefit for adult patients with locally advanced head and neck squamous cell carcinoma (HNSCC). We aim to investigate if adjuvant RT provides a similar survival advantage to patients ages 80+ through a national curated database. Methods This retrospective cohort study queried the National Cancer Database (NCDB) for all cases of HNSCC between 2004-2016. Patients treated with surgical resection alone were compared to those treated with surgery plus adjuvant RT. Overall survival (OS) was compared within adult (age <80 years) and senior adult (age ≥80 years) cohorts using Kaplan-Meier analysis. Hazard ratios (HR) were assessed using Cox proportional hazards to account for differences in patient characteristics, primary site, and HNSCC stage. Results NCDB identified 16,504 locally advanced HNSCC treated with definitive surgery with 9,129 (55.3%) also receiving adjuvant RT. The mean age was 63.8 years (SD = 12.0) with 88.7% of patients ages <80 years and 11.3% ages ≥80 years. In the adult cohort, adjuvant RT was associated with a significant increase in OS compared to surgery alone at 1 year (88.4% vs. 83.8%, p=<0.001), 3 years (64.0% vs. 59.2%, p=<0.001) and 5 years (52.8% vs. 47.2%, p=<0.001). Treatment with surgery alone remained a significant predictor of mortality risk at 1 year (HR 1.48, 95% CI 1.35-1.64, p<0.001), 3 years (HR 1.25, 95% CI 1.18-1.33, p<0.001), and 5 years (HR of 1.23, 95% CI 1.17-1.30, p=<0.001). In the senior adult cohort, there were no significant differences in OS between treatment groups at 1 year (73.4% vs. 74.8%, 0.296), 3 years (45.8% vs. 41.8%, p=0.465), or 5 years (28.2% vs. 27.7% p=0.759). Treatment with surgery alone was not a significant predictor of mortality risk at 1 year (HR 1.11, 95% CI 0.90-1.36, p=0.316), 3 years (HR 0.94, 95% CI 0.81-1.08, p=0.423), or 5 years (HR 0.95, 95% CI 0.83-1.08, p=0.476). Conclusion The addition of adjuvant RT in senior patients (age ≥80 years) may not provide a similar OS benefit to that observed in younger patients. Further research is needed to best guide shared-decision making in this population.